Co-disposal of magnesium slag and high-calcium fly ash as cementitious materials in backfill. (10th January 2021) - Liu, Lang; Ruan, Shishan; Qi, Chongchong; Zhang, Bo; Tu, Bingbing; Yang, Qixing; Song, K.I.-I.L.
Abstract: Waste minimization is a major approach whereby many industries decrease environmental pollution and promote cleaner production. To achieve sustainable development, a novel idea is proposed herein to recycle magnesium slag (MS) and high-calcium fly ash (FA) into cementitious materials which are then mixed with aeolian sand (AS) to produce a type of paste backfill (MFPB) material that can be used in the mining industry. The rheological and mechanical properties of backfill materials with different FA contents were investigated. The results reveal that: (1) fresh MFPB mortars with different proportions conformed to the Herschel–Bulkley model. The yield stress initially decreased, and then increased with rising FA content. When the FA content was less than 20 wt%, the rheology of the MFPB surpassed that of the pure MS mortar, and an FA content of 10 wt%, yielded the best rheological properties of the fresh MFPB mortar. The mini-slump value, which was between 108 mm (MS-FA0) and 141 mm (MS-FA10), first increased and then decreased with increasing FA content. (2) The unconfined compressive strength (UCS) increased with extended curing times and FA contents, as well as the early-age strength development, which accelerated with increasing FA content. The UCS at 28 d escalated from 2.607 MPa (MS-FA0) to 7.491 MPa (MS-FA40). (3) The microstructure of the MFPB samples was discovered to agree with the UCS results. X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) were conducted to investigate the hydration products of the MFPB samples. The hydration mechanism of the MS and FA mixture was discussed, and the former was less reactive when used individually, although its reactivity increased with the addition of high-calcium FA. CaO dissolution in the MS and FA led to the generation of Ca(OH)2, which was a prerequisite for the successive pozzolanic reaction between the MS and FA. This study investigated the feasibility of the co-disposal of MS and FA, which could significantly promote a cleaner mineral production, and mining industry, when used together with backfill technology. Graphical abstract: Image 1 Highlights: The co-disposal of MS and FA as cementitious materials was proposed. The cementitious materials were used with AS to produce backfill materials. The rheological and mechanical properties of backfill materials were investigated. The MS-FA was found to have sufficient cementitious property. The mechanism of strength development was studied through microscopic analysis.